Influence of the noncondensable component on the characteristics of temperature change and the intensity of water droplet evaporation. (December 2018) - Levashov, Vladimir Yu.; Kryukov, Alexei P.; Shishkova, Irina N.
Highlights: This paper suggests an approach to solve for the problem of liquid droplets evaporating into a vapor–gas mixture. The proposed solution is based on the direct numerical solutions of a system of two Boltzmann kinetic equations, and conservation laws for a droplet in this scenario is suggested. This approach makes it possible to approximate the evolutions of droplet size and temperature. The proposed method was validated by applying it to approximate the evolution of the evaporation of real water droplets into a vapor (water)-gas (air) mixture at atmospheric pressure. The calculated droplet size and temperature evolutions agreed reasonably well with the experimental data. Abstract: The removal of vapor molecules from a droplet surface is an important stage of evaporation in a vapor–gas mixture. In this work, with the evaporation of a water droplet in a vapor–gas medium as the example, the influence of the noncondensable component on the intensity of the evaporation process and the characteristics of the temperature change is examined. The heat supplied to an interface is often assumed to be entirely utilized for evaporation, with the formed vapor removed from the evaporation surface through diffusion. However, the diffusion flux develops at a distance of some mean free paths of vapor molecules away from the evaporation surface, that is, in the Knudsen layer. In this layer, because of intermolecular collisions, the molecule–velocity distribution undergoes substantial changes, which are calculated using the methods of physical kinetics. Herein, the system of two Boltzmann kinetic equations for a vapor–gas mixture is used for calculating mass flux density of the evaporating substance near the evaporation surface. The calculation results are then compared with published experimental data.